Strategi Pembelajaran Interaktif Dalam Meningkatkan Kemampuan Menghafal Al-Qur’an Di SMP IT Pondok Tahfidzh Qur’an Permis Tahun Ajaran 2023/2024 - Uci Rahmadini (Al-Abshor : Jurnal Pendidikan Agama Islam, 2025)
Memorizing the Qur'an is one of the important aspects in education in Islamic boarding schools. In practice, memorizing the Qur'an is not an easy task. The memorization process that requires perseverance, patience and high discipline is often a challenge for students or students in Islamic boarding schools. The purpose of this study is to determine interactive learning strategies in improving the ability to memorize the Qur'an and to find out what challenges are faced in interactive learning strategies in improving the ability to memorize the Qur'an at SMP IT Pondok Tahfidzh Qur'an Permis. The method used in this study is a qualitative method with a descriptive approach. Data collection techniques are carried out using observation, interview, and documentation methods. While the data analysis technique is by data reduction (data reduction), data display and drawing conclusions/verification (drawing conclusions). The respondents in this study were tahfidzh teachers, namely five (5) teachers and students of SMP IT Pondok Tahfidzh Qur'an Permis, grade eight, totaling 86 students. The results of this study show that the learning strategies used to improve the ability to memorize the Qur'an at the SMP IT Permis Islamic Boarding School are learning in groups, a holistic approach, and an emotional and spiritual approach. Meanwhile, the challenges faced in improving the ability to memorize the Qur'an are that students do not yet have good abilities in reading or memorizing the Qur'an. In addition, it also takes a long time to improve memorization in the midst of students' busy schedules, students are difficult to work together and there is a lack of seriousness in memorizing the Qur'an. Abstrak Menghafal Al-Qur’an bukanlah tugas yang mudah. Proses menghafal yang membutuhkan ketekunan, kesabaran dan disiplin tinggi seringkali menjadi tantangan bagi para peserta didik atau santri di pondok pesantren. Tujuan penelitian ini adalah mengetahui strategi pembelajaran interaktif dalam meningkatkan kemampuan menghafal Al-Qur’an dan mengetahui hambatan apa yang dihadapi dalam strategi pembelajaran interaktif dalam meningkatkan kemampuan menghafal Al-Qur’an di SMP IT Pondok Tahfidzh Qur’an Permis. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data yang dilakukan dengan metode observasi, wawancara, dan dokumentasi. Sedangkan teknik analisis data yaitu dengan data reduction (reduksi data), data display dan conclusion drawing/verification (menarik kesimpulan). Responden penelitian ini adalah guru tahfidzh yaitu sebanyak lima (5) guru dan peserta didik SMP IT Pondok Tahfidzh Qur’an Permis kelas delapan yang berjumlah 86 siswa. Hasil penelitian ini diketahui bahwa strategi pembelajaran yang digunakan dalam meningkatkan kemampuan menghafal Al-Qur’an di Pondok Psantren SMP IT Permis yaitu belajar dalam kelompok, pendekatan holistik dan pendekatan emosional dan spiritual. Siswa memerlukan waktu yang cukup lama dalam meningkatkan hafalan ditengah waktu peserta didik yang padat, peserta didik sulit diajak untuk bekerjasama dan adanya ketidakseriusan dalam menghafal Al-Qur’an.